PARENT-CHILD RELATIONSHIP AS A PREDICTOR OF ADOLESCENTS’ INVOLVEMENT IN ANTISOCIAL BEHAVIOUR IN SELECTED SECONDARY SCHOOLS IN MAKUENI COUNTY, KENYA - MILCAH WAENI MUTUKU (Machakos University Press, 2025)
The study considered an dolescent as any individual aged between 12 and 19 years. This is a critical transition period between childhood and adulthood, where there is rapid growth and significant changes in the physical, psychological, emotional, intellectual and social domains. The general objective of this study was to investigate parent-child relationship as a predictor of adolescents’ involvement in antisocial behaviour in selected public secondary schools in Makueni County, Kenya. The specific objectives of study were to; investigate the degree to which monitoring parent child relationship, supportive parent-child relationship, strict parent-child relationship, and the neglecting parent-child relationship can predict the adolescents’ involvement in antisocial behaviour. The study was grounded on the social bonding theory by Hirschis (1969). To achieve these objectives, a sample of 458 participants was selected consisting of students, school principals, deputy school principals, guidance and counseling masters, parents and guardians from the sampled schools. Purposive, Stratified and simple random sampling methods were applied in selecting the participants. Oral interview schedule, documentary reports and the respondents’ questionnaires were used as data collection instruments. Based on the study findings, 83.8% of the students interviewed had exhibited at least one of the antisocial behaviours, where 57.85% were boys and 42.15% were girls. Boarding schools had a higher occurrence of antisocial behaviours compared to day mixed secondary schools. Based on the school principals’ interview schedule and the documentary records, stealing and disobedient to teachers were the most rampant followed closely by the examination cheating and drugs and substance abuse antisocial behaviours. The study findings showed that both the monitoring parent-child relationship and the supportive parent-child relationship had an inverse and significant relationship with the adolescent antisocial behaviour, having a Pearson correlation coefficient values of -0.28 and -0.24 respectively (p = 0.00). The neglecting parent-child relationship had a significant but direct relationship with adolescent antisocial behaviour with a Pearson correlation value of 0.18 (p = 0.05). The strict parent-child relationship had an inverse relationship with the adolescent antisocial behaviour but was not significant at 5% significance level. Only the monitoring parent-child relationship and the neglecting parent-child relationship were significant in the multiple regression model with (-1.35) and (+1.01) regression coefficients respectively alongside gender and the school category where mixed secondary schools were better off. Therefore among the four predictor variable under investigation, only the monitoring parent-child and neglecting parent-child relationships could predict the antisocial behavior significantly at 𝛼 = 0.05. It was established that peer pressure, poor parenting, mass media and unclear policy guideline from the Ministry of Education on how to handle some of the adolescent antisocial behaviours were to blame for increased antics among the secondary school adolescents. It was recommended that open school forums for parents and their sons or daughters, in-service staff training, and clear policy guidelines by the Ministry of Education should be availed. The study suggested that similar research but in different counties and institutions should be conducted to ascertain the results and generalizability of the findings